Т.Шевченко як об'єкт психоаналітичних розвідок - Кошелюк, Олена; Kosheliuk, Olena (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті пропонується зріз психоаналітичних розвідок від початку ХХ століття й по сьогодні, об’єктом дослідження яких стала постать Т. Шевченка. Нова віха у дослідженнях творчості митця не випадково виявилася маркованою з позицій психоаналітичного вчення; останнє дає щораз цікаві й дискусійні інтерпретаційні моделі. The article is devoted to the psychoanalytical investigations since the beginning of the twentieth century and to nowadays, in which the research object is a person of T. Shevchenko. New direction in the study of creativity of the artist is marked by psychoanalytical approach; and it’s not an accident. It proposes interesting and controversial interpretation models. Bright personalities were always in zone of psychoanalytical interest. The objects of psychoanalytical investigations are modern and distinguished artists such as V. Vynnychenko, V. Domontovych, L. Kostenko, A. Khrymsky, I. Nechuy-Levitsky, T. Osmachka, Lesia Ukrainka, I. Franko, T. Shevchenko and others. Particular attention is needed for Shevchenkological investigations in psychoanalytic field – such of researches are the most popular among other psychoanalytical. Shevchenkological psychoanalysis originated in the early twentieth century with the work of S. Baley and still actively developed, giving interesting interpretations of the writer’s creative work. We can talk about two stadiums in the history of psychoanalytic research on T. Shevchenko: the first one chronologically covers the 10−30th years of XX century (study S. Baley, A. Haletsky, J. Yarema), the second – late 80’s to nowadays (the works of L. Pliushch, G. Hrabovych, M. Laslo- Kutsiuk, O. Zabuzhko). Early stage of psychoanalytic shevchenkological studies the person of T. Shevchenko records as an interesting phenomenon for understanding the nature of psychology genius of the artist, while the modern stage is based on «dethrone, disprove, decanonnizate». It is clear that these extremes – a tribute to the development and establishment of the shevchenkological psychoanalysis, while building a constructive research methodology writers’ works and new psychoanalytic reading of the work are now in time.
T. Shevchenko as object for psychoanalytical investigations
Keywords: психоаналіз; несвідоме; колективне несвідоме; архетип; архетипний образ